Assistive Technology as Affective Scaffolding - Candiotto, Laura; Stapleton, Mog (Springer Nature Switzerland AG, 2024)
In this paper, we argue that the affective experience that permeates the employment of Assistive Technology (AT) in special needs education is crucial for the integration of AT. "AT integration" generally means the fluid and automatic employment of AT for fulfilling certain tasks. Pritchard et al. (2021) have proposed a more specific conceptualisation of AT integration by saying that AT is integrated when it is part of the user's cognitive character. By discussing their proposal, we argue that the user's affective experience is crucial for AT integration. To better appreciate the relevance of the affective experience in AT integration, we suggest shifting the perspective from the functionalist extended cognition framework, as Pritchard et al. (2021) propose, to affective scaffoldings. In doing so we focus on the feeling of agency as the key experience to consider for understanding what AT does to the agent. We will put forth the hermeneutical tool of "phenomenal transformation" to explain how and why AT as an affective scaffolding can support the fundamental "I can" of the experience.
Asistenční technologie jako afektivní lešení
Keywords: Assistive technology; Cognitive integration; Extended mind; Affective scaffoldings; Feeling of agency; Existential necessity; Phenomenal transformation; Asistenční technologie; kognitivní integrace; rozšířená mysl; afektivní lešení; pocit děje; existenciální nutnost; fenomenální transformace.